MOF (Metal Organic Framework) derived copper-based catalyst, and preparation method and application thereof

By using MOF-derived copper-based catalysts, the problems of insufficient activity of existing catalysts at high temperatures and high cost of precious metal catalysts are solved, and the hydrogen production effect of methanol liquid phase reforming under medium and low temperature conditions is achieved. .

CN119425690APending Publication Date: 2025-02-14DONGGUAN UNIV OF TECH

Patent Information

Application Number
CN202411559928.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing methanol liquid-phase reforming hydrogen production catalysts are insufficient at high temperatures, and the precious metal catalysts are costly, while non-precious metal catalysts are poor at low temperatures, making it difficult to meet the needs of high efficiency, low cost and high selectivity.

Method used

By using metal organic framework material (MOF) as templates, a copper-based catalyst with high specific surface area, rich pore structure and highly dispersed are prepared. Cu/C catalyst with a micromesoporous structure is formed after high-temperature carbonization using Cu-MOF material. .

Benefits of technology

It realizes efficient catalytic methanol liquid phase reforming under medium and low temperature conditions to produce hydrogen, and the catalyst has good stability and selectivity and is low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425690A_ABST
    Figure CN119425690A_ABST
Patent Text Reader

Abstract

The invention discloses an MOF-derived copper-based catalyst and a preparation method and application thereof.According to the MOF-derived copper-based catalyst, a Cu-MOF metal organic framework material synthesized through hydrothermal reactions in different modes serves as a sacrifice template agent, a series of copper-based catalytic materials with rich micro-mesoporous structures are prepared through high-temperature calcination, copper particles of the obtained materials are highly dispersed, the specific surface area is high, and the molecular weight is high; the size of the metal Cu can reach the nanoscale, the metal content can reach 45%, when the catalyst is used for catalyzing the methanol liquid phase reforming hydrogen production reaction, no CO or CH4 byproduct gas is generated in the whole hydrogen production process, and the stability and the service life of the catalyst are superior to those of a common copper-based metal catalyst; the invention provides an efficient and low-cost non-noble metal catalyst for medium-low temperature methanol liquid phase reforming hydrogen production, and has certain significance for the development of subsequent low temperature methanol liquid phase reforming hydrogen production catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a MOF-derived copper-based catalyst, a preparation method and application thereof, and in particular to application in hydrogen production by liquid phase reforming of methanol. Background Art

[0002] China is the largest producer of methanol, with a production capacity of 60% of the world's total. The industry is mature, large-scale, low-cost, and has a guaranteed supply of raw materials. Methanol is a liquid at room temperature and pressure, with a high hydrogen storage density. In addition, the storage and transportation costs and safety advantages make it the most suitable hydrogen production raw material for my country's energy structure. In the methanol reforming hydrogen production system, methanol can be converted into hydrogen through a variety of methods, mainly divided into methanol steam reforming (MSR), methanol partial oxidation (POM) and methanol autothermal reforming (OMR). Among them, methanol steam reforming hydrogen production technology is the most mature and has the widest application range. The operating temperature of the MSR hydrogen production process reported so far is generally higher than 250°C. The relatively high operating temperature and vaporization unit lead to a slow start-up of the distributed methanol hydrogen production system. Therefore, methanol liquid phase reforming hydrogen production has become a research hotspot.

[0003] Common methanol reforming hydrogen production catalysts can be divided into two categories. One category is precious metal catalysts represented by Pt, Pd, etc., which have the advantages of strong stability, high activity, and low selectivity for CO and CH4. However, the reserves of precious metal resources are scarce, and their high prices will undoubtedly increase the cost of methanol reforming hydrogen production process, so they are not suitable for large-scale application. The other category is copper-based non-precious metal catalysts, which have the advantages of high activity, good selectivity and low cost and have become the most popular methanol hydrogen production catalyst. At present, the CuO / ZnO / Al2O3 ternary catalyst is used on a large scale in industry, but this catalyst will only show high activity when the reaction temperature is >300℃. The common copper-based catalyst preparation method is the form of precipitation and sintering. Due to the poor controllability of the precipitated metal in an alkaline environment, the obtained metal particles are unevenly dispersed, the particles are obviously agglomerated, and the catalyst activity is poor. Therefore, the preparation of efficient, highly selective, highly stable and low-cost methanol liquid phase reforming hydrogen production catalysts is an urgent problem to be solved. Summary of the invention

[0004] Based on the needs and deficiencies of the prior art, the present invention provides a MOF-derived copper-based catalyst, a preparation method and an application thereof, wherein the application is application in hydrogen production by liquid phase reforming of methanol; the catalyst uses a metal organic framework material as a sacrificial template, and obtains a catalyst with highly dispersed non-precious metals and high specific surface area by regulating high-temperature carbonization conditions, and the metal particle size can reach nanometer or sub-nanometer level.

[0005] In order to achieve the purpose of the present invention, the present invention provides the following technical solutions:

[0006] A MOF-derived copper-based catalyst, wherein the MOF-derived copper-based catalyst is a micro-mesoporous structure Cu / C, wherein the mesopores are distributed in 3-20nm and the micropores are distributed in 0.1-10.8nm; the MOF-derived copper-based catalyst particle size is 2-15μm; the specific surface area is 25-981m 2 / g; the metal copper particles have a size of 5-500nm and are evenly distributed on the carbon material;

[0007] Furthermore, the mesopores are distributed in the range of 4.5-16.3 nm, the micropores are distributed in the range of 0.3-0.5 nm; the MOF-derived copper-based catalyst particle size is 5-10 μm; the specific surface area is 100-800 m 2 / g; the metal copper particle size is 50-300nm.

[0008] Furthermore, the mesopores are distributed at 10 nm, the micropores are distributed at 0.4 nm; the MOF-derived copper-based catalyst particle size is 7.5 μm; the specific surface area is 103.2 m 2 / g; the metal copper particle size is 70nm.

[0009] The second object of the present invention is to provide a method for preparing the above-mentioned MOF-derived copper-based catalyst, the method for preparing the MOF-derived copper-based catalyst comprising the following steps:

[0010] (1) Synthesis of copper-based metal organic framework materials (Cu-MOF materials): copper salt, organic ligand, and chelating agent are dissolved in a certain amount of solvent to prepare a mixed solution, the mixed solution is transferred into a reaction container and placed in an oven for crystallization reaction, and after the reaction is completed, the mixed solution is cooled, filtered, washed, and dried to obtain the Cu-MOF material;

[0011] (2) Preparation of MOF-derived copper-based catalyst: The Cu-MOF material obtained in step (1) is ground evenly and placed in a porcelain boat, which is then placed in a high-temperature tubular furnace containing a protective atmosphere for high-temperature calcination and carbonization treatment. After a period of time, the solid subjected to high-temperature calcination and carbonization treatment is taken out and ground evenly to obtain the MOF-derived copper-based catalyst.

[0012] Furthermore, the solvent in step (1) is one or more of deionized water, anhydrous ethanol, methanol, N,N-dimethylformamide, and tetrahydrofuran.

[0013] Furthermore, the copper salt in step (1) is one or more of copper nitrate, copper acetate, copper chloride, copper sulfate, and copper acetylacetonate;

[0014] Furthermore, the organic ligand in step (1) is one or more of trimesic acid (BTC), terephthalic acid (BDC), isophthalic acid, phthalic acid, aminoterephthalic acid (NH2-BDC), and nitroterephthalic acid (NO2-BDC);

[0015] Furthermore, the chelating agent in step (1) is one or more of polyvinyl pyrrolidone (PVP, Mw=8000-220000), polyethers (such as F127, P123), cetyltrimethylammonium bromide (CTAB), cetyltrimethylammonium chloride (CTAC), lauric acid, acetic acid, formic acid, triethylamine, diethylamine, and sodium formate;

[0016] Furthermore, the protective atmosphere is nitrogen or argon.

[0017] Furthermore, the crystallization reaction in step (1) is carried out in a crystallization kettle, in a glass container placed in a water bath or an oil bath, or with ultrasound assistance; and the crystallization reaction temperature is 80-180°C.

[0018] Furthermore, in step (1), the molar ratio of the copper salt to the organic ligand is 1:(0.4-25), the molar ratio of the copper salt to the solvent is 1:(10-680), and the molar ratio of the copper salt to the chelating agent is 1:(0.5-60).

[0019] Furthermore, the high temperature carbonization treatment temperature in step (2) is 300-1000°C, the carbonization time is 1-12h, and the heating rate is 0.5-10°C / min.

[0020] The third object of the present invention is to provide an application of the above-mentioned MOF-derived copper-based catalyst, wherein the application is an application in a methanol liquid phase reforming hydrogen production reaction, wherein the application uses a methanol solution as a raw material and produces H2 under the action of a Cu / C catalyst;

[0021] The reaction process includes the following steps:

[0022] Step 1: First, 10-100 mg of the catalyst sample is reduced and activated at 250°C for 1-3 hours in high-purity hydrogen at a flow rate of 10-100 mL / min. After the catalyst is cooled to room temperature, 5-15 mL of methanol aqueous solution is added to the reaction system to seal the activated catalyst sample;

[0023] Step 2: Add a small amount of additives to the reaction system to absorb the CO2 produced by the reaction to promote the forward progress of the reaction. Purge the reactor three times with 2MPa inert gas as a protective gas and then seal the reactor to maintain a pressure of 2MPa;

[0024] Step 3: Then the reactor is heated to a temperature of 150-250°C for 1-3 hours. After the reaction is completed, the reactor is taken out and quickly cooled to room temperature, and the gas phase product is collected. The gas phase product is quantitatively analyzed using a gas chromatograph with a single-point calibration method.

[0025] Furthermore, the reaction temperature range of step 2 is 190-230° C., and the reaction pressure is 2 MPa; the volume ratio of methanol to water in the methanol aqueous solution is 1:1-5.

[0026] Furthermore, the auxiliary agent in step 2 includes one or more of NaOH, KOH, K2CO3, Na2CO3 and ethylenediamine.

[0027] Compared with the existing technology, the beneficial effects of this application are:

[0028] 1) The present invention uses copper salt as a copper source, selects organic molecules containing functional groups such as carboxyl groups as organic ligands, and self-assembles into metal organic framework materials. By adjusting the pyrolysis conditions, the Cu-MOF material is used as a sacrificial template to prepare a MOF-derived copper-based supported carbon catalytic material with a large specific surface area, high porosity, and highly dispersed metallic copper; the rich micro-mesoporous structure provides sufficient space for the methanol reforming hydrogen production reaction; the highly dispersed metal particles are a strong guarantee for the excellent catalytic activity and selectivity of the catalyst, and the preparation method is simple and controllable, the raw materials are easily available, and the cost is low.

[0029] 2) The catalytic material obtained by the present invention has a large specific surface area and a rich pore structure, which is beneficial to increase the mass transfer and diffusion capacity of reactants and products, and provides sufficient space for the methanol liquid phase reforming hydrogen production reaction; the copper particles of the obtained material are highly dispersed and have a high specific surface area, the metal Cu size can reach nanometer level, and the metal content can reach 45%; the metal copper is highly dispersed, the methanol hydrogen production performance is good, and the CO selectivity is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the scheme in the embodiment of the present invention, the catalytic material obtained in Example 1 will be briefly introduced in the form of drawings.

[0031] Figure 1 This is the wide-angle XRD pattern of the Cu-MOF material and Cu / C catalyst obtained in Example 1 of the present invention.

[0032] Figure 2 The SEM image (left) and TEM image (right) of the Cu / C catalyst obtained in Example 1 of the present invention.

[0033] Figure 3 This is the N2 physical adsorption diagram of the Cu / C catalyst obtained in Example 1 of the present invention.

[0034] Figure 4This is the Cu 2p XPS graph of the Cu / C catalyst obtained in Example 1 of the present invention.

[0035] Figure 5 Graph showing the hydrogen production rate of the Cu / C catalysts obtained in Examples 10-20.

[0036] Figure 6 This is a graph showing the hydrogen production rate and stability of the Cu / C catalyst obtained in Example 21 in the catalytic methanol liquid phase reforming hydrogen production reaction.

[0037] Figure 7 Graphs showing methanol conversion, hydrogen selectivity, and carbon monoxide selectivity of the Cu / C catalysts obtained in Examples 10-20. DETAILED DESCRIPTION

[0038] In order to make the purpose and technical solution of the present invention clearer, the present invention will be described in detail below in conjunction with Examples 1-21, but the content included in the present invention is not limited to the embodiments given below. Based on the embodiments in the present invention, all other embodiments obtained by relevant researchers in this field without making creative work are within the scope of protection of this application. In the absence of conflict, the following embodiments and their technical features can be combined with each other.

[0039] Example 1

[0040] A method for preparing a MOF-derived copper-based catalyst comprises the following steps: (1) dissolving 1.75 g of Cu(NO3)2·3H2O and 0.5 g of CTAB in 30 ml of deionized water, referred to as solution A; dissolving 0.85 g of terephthalic acid (H3BDC) in 30 ml of anhydrous ethanol, referred to as solution B; stirring the two solutions evenly, adding solution B to solution A to obtain a mixed solution, placing the mixed solution into a 100 ml hydrothermal reactor with a polytetrafluoroethylene liner and placing the mixed solution in an oven, crystallizing the mixed solution at 110° C. for 10 h, taking the mixed solution out and cooling the mixed solution, washing the mixed solution with water and ethanol for three times respectively, and drying the mixed solution in a vacuum oven at 90° C. to obtain a Cu-MOF material;

[0041] (2) Grinding the Cu-MOF material obtained in step (1) uniformly and placing it in a N2 protective atmosphere tubular furnace, slowly heating it to 900°C at a heating rate of 2°C / min, and calcining it for 2h to obtain the MOF-derived copper-based catalyst.

[0042] Figure 1 (Left) is the XRD pattern of Cu-MOF synthesized in step (1) of Example 1, Figure 1 (Right) is the XRD pattern of the Cu / C catalyst obtained in Example 1. It can be seen that Cu-MOF can be completely carbonized after high-temperature pyrolysis, and a metallic Cu phase and a weak Cu2O phase are produced, indicating that the Cu in MOF 2+was successfully reduced to metallic Cu, but a small amount of Cu 2+ reacted with the O atoms in the framework to form Cu2O.

[0043] Figure 2 SEM and TEM images of the Cu / C catalyst obtained in Example 1 are shown. It can be seen that the particle size of the Cu / C catalyst obtained in Example 1 is about 7.5 μm; Figure 2 The TEM image shows that the size of the metal in the material after carbonization reduction is about 70 nm, and these metal particles are uniformly distributed on the carbon material.

[0044] Figure 3 N2 adsorption-desorption isotherm curves of the Cu / C material obtained in Example 1 are shown. An obvious hysteresis loop appears in this figure, indicating that the material has abundant micropores and mesopores. The mesopores are distributed around 4.5 and 16.3 nm, and the micropores are distributed around 0.4 nm.

[0045] Figure 4 Cu 2p XPS spectra of the Cu / C material obtained in Example 1 are shown. The Cu 2p spectrum is divided into Cu(0<x<1) (~932.7 eV) and Cu(II) (~934 eV). The presence of the Cu(II) peak may be due to the surface oxidation of Cu species during the passivation process.

[0046] The above characterization results show that the MOF-derived copper-based catalyst Cu / C prepared in Example 1 has a relatively high specific surface area (the specific value is 103.2 m 2 / g), and has an abundant micropore-mesopore structure. The Cu in the MOF 2+ is mainly reduced to metallic Cu and Cu + phases. The size of the metallic Cu particles is nanoscale and uniformly dispersed. This MOF-derived copper-based catalyst will play a significant application value in methanol steam reforming for hydrogen production.

[0047] Example 2

[0048] A preparation method of a MOF-derived copper-based catalyst, comprising the following steps: (1) Dissolve 2.1 g of Cu(NO3)2·3H2O in 35 ml of DMF, denoted as solution A; dissolve 1.5 g of terephthalic acid (H2BDC) and 0.75 g of PVP (Mw = 10000) in 35 ml of DMF, denoted as solution B; after stirring evenly, add solution B to solution A to obtain a mixed solution. Load the above mixed solution into a 100 ml hydrothermal reaction kettle with a polytetrafluoroethylene liner and place it in an oven. After crystallization at 85 °C for 40 h, take it out, wash it 3 times with absolute ethanol, and place it in a vacuum oven at 80 °C for drying to obtain a Cu-MOF material;

[0049] (2) The Cu-MOF material obtained in step (1) was evenly ground and placed in a N2 protective atmosphere tubular furnace, and the temperature was slowly increased to 700°C at a heating rate of 2°C / min. After calcination for 4 hours, the MOF-derived copper-based catalyst was obtained.

[0050] Example 3

[0051] A preparation method of a MOF-derived copper-based catalyst comprises the following steps: (1) dissolving 1.75 g of Cu(Ac)2·H2O and 0.5 g of CTAB in 40 ml of deionized water, referred to as solution A; and dissolving 0.9 g of trimesic acid (H3BTC) in 30 ml of anhydrous ethanol, referred to as solution B; after stirring them respectively and uniformly, adding solution B to solution A to obtain a mixed solution, charging the mixed solution into a 100 ml hydrothermal reactor with a polytetrafluoroethylene liner and placing the mixed solution in an oven, crystallizing at 140° C. for 12 h, taking the mixed solution out, washing the mixed solution with anhydrous ethanol for 3 times, and drying the mixed solution in a vacuum oven at 60° C. to obtain a Cu-MOF material;

[0052] (2) Grinding the Cu-MOF material obtained in step (1) uniformly and placing it in a N2 protective atmosphere tubular furnace, slowly heating it to 700°C at a heating rate of 2°C / min, and calcining it for 2h to obtain the MOF-derived copper-based catalyst.

[0053] Example 4

[0054] A preparation method of a MOF-derived copper-based catalyst comprises the following steps: (1) dissolving 1.75 g of Cu(Ac)2·H2O and 0.5 g of CTAB in 40 ml of deionized water, referred to as solution A; and dissolving 0.95 g of terephthalic acid in 30 ml of anhydrous ethanol, referred to as solution B; after stirring them evenly, adding solution B to solution A to obtain a mixed solution, placing the mixed solution into a 100 ml hydrothermal reactor with a polytetrafluoroethylene liner and placing the mixed solution in an oven, crystallizing at 140° C. for 12 h, taking the mixture out, washing it with anhydrous ethanol for 3 times, and drying it in a vacuum oven at 60° C. to obtain a Cu-MOF material;

[0055] (2) Grinding the Cu-MOF material obtained in step (1) uniformly and placing it in a N2 protective atmosphere tubular furnace, slowly heating it to 800°C at a heating rate of 2°C / min, and calcining it for 2h to obtain the MOF-derived copper-based catalyst.

[0056] Example 5

[0057] A method for preparing a MOF-derived copper-based catalyst comprises the following steps: (1) dissolving 1.5 g of Cu(Cl)2·H2O and 0.45 g of F127 in 50 ml of deionized water, referred to as solution A; and dissolving 1.05 g of trimesic acid (H3BTC) in 50 ml of anhydrous ethanol, referred to as solution B; stirring the mixtures evenly, adding solution B to solution A to obtain a mixed solution, placing the mixed solution in a 250 ml round-bottom flask and placing the mixed solution in an oil bath at 150° C. for reaction for 36 hours, taking the mixed solution out, washing the mixture with anhydrous ethanol for 3 times, and drying the mixture in a vacuum oven at 60° C. to obtain a Cu-MOF material;

[0058] (2) Grinding the Cu-MOF material obtained in step (1) uniformly and placing it in a N2 protective atmosphere tubular furnace, slowly heating it to 700°C at a heating rate of 2°C / min, and calcining it for 2h to obtain the MOF-derived copper-based catalyst.

[0059] Example 6

[0060] A method for preparing a MOF-derived copper-based catalyst comprises the following steps: (1) dissolving 2.1 g of Cu(NO3)2·3H2O and 0.5 g of CTAB in 35 ml of deionized water, referred to as solution A; and dissolving 1.5 g of aminoterephthalic acid (NH2-H2BDC) in 30 ml of deionized water, referred to as solution B; stirring the mixtures evenly, adding solution B to solution A to obtain a mixed solution, placing the mixed solution into a 100 ml hydrothermal reactor with a polytetrafluoroethylene liner and placing the mixed solution in an oven, crystallizing at 120° C. for 48 h, taking the mixture out, washing the mixture with anhydrous ethanol for 3 times, and drying the mixture in a vacuum oven at 100° C. to obtain a Cu-MOF material;

[0061] (2) The Cu-MOF material obtained in step (1) was evenly ground and placed in a N2 protective atmosphere tubular furnace, and the temperature was slowly increased to 800°C at a heating rate of 2°C / min. After calcination for 4 hours, the MOF-derived copper-based catalyst was obtained.

[0062] Example 7

[0063] A method for preparing a MOF-derived copper-based catalyst comprises the following steps: (1) dissolving 2.09 g of Cu(C5H7O2)2 in 100 ml of deionized water, referred to as solution A; and dissolving 1.16 g of H3BTC in 100 ml of deionized water, referred to as solution B; stirring the two solutions evenly, adding solution B to solution A to obtain a mixed solution, adding 0.2 g of sodium formate to the mixed solution, and placing the mixed solution in a 500 ml round-bottom flask, stirring at room temperature for crystallization for 60 hours, taking out the solution, washing it with anhydrous ethanol for 3 times, and drying it in a vacuum oven at 80°C to obtain a Cu-MOF material;

[0064] (2) Grinding the Cu-MOF material obtained in step (1) uniformly, placing it in a N2 protective atmosphere tube furnace, slowly heating it to 900°C at a heating rate of 2°C / min, and calcining it for 4 hours to obtain the MOF-derived copper-based catalyst.

[0065] Example 8

[0066] A preparation method of a MOF-derived copper-based catalyst comprises the following steps: (1) dissolving 2.09 g of Cu(NO3)2·3H2O in 75 ml of deionized water, referred to as solution A; and dissolving 1.16 g of H3BTC in 75 ml of deionized water, referred to as solution B; stirring the two solutions evenly, adding solution B to solution A to obtain a mixed solution, adding 0.62 ml of formic acid to the mixed solution, and placing the mixed solution in a 250 ml round-bottom flask, stirring at room temperature for crystallization for 48 hours, taking out the solution, washing it with anhydrous ethanol for 3 times, and drying it in a vacuum oven at 80°C to obtain a Cu-MOF material;

[0067] (2) The Cu-MOF material obtained in step (1) was evenly ground and placed in a N2 protective atmosphere tubular furnace, and the temperature was slowly increased to 800°C at a heating rate of 2°C / min. After calcination for 4 hours, the MOF-derived copper-based catalyst was obtained.

[0068] Example 9

[0069] A method for preparing a MOF-derived copper-based catalyst comprises the following steps: (1) dissolving 2.09 g of Cu(NO3)2·3H2O in 25 ml of deionized water, referred to as solution A; and dissolving 1.16 g of H3BTC in 25 ml of deionized water, referred to as solution B; stirring the two solutions evenly, adding solution B to solution A to obtain a mixed solution, adding 3 ml of diethylamine to the mixed solution, and placing the mixed solution in a 100 ml round-bottom flask, crystallizing at 120° C. for 40 h, taking out the solution, washing it with anhydrous ethanol for 3 times, and drying it in a vacuum oven at 80° C. to obtain a Cu-MOF material;

[0070] (2) The Cu-MOF material obtained in step (1) was evenly ground and placed in a N2 protective atmosphere tubular furnace, and the temperature was slowly increased to 700°C at a heating rate of 2°C / min. After calcination for 4 hours, the MOF-derived copper-based catalyst was obtained.

[0071] Comparative Example 1

[0072] (1) 2.09 g Cu(NO3)2·3H2O was dissolved in 25 ml deionized water, which was recorded as solution A; 1.16 g H3BTC was dissolved in 25 ml deionized water, which was recorded as solution B; the two solutions were stirred evenly, solution B was added to solution A to obtain a mixed solution, 3 ml diethylamine was added to the mixed solution, and the solution was placed in a 100 ml round-bottom flask, crystallized at 120°C for 40 h, then taken out, washed with anhydrous ethanol three times, and dried in a vacuum oven at 80°C to obtain a Cu-MOF material;

[0073] (2) The Cu-MOF material obtained in step (1) was evenly ground and placed in a N2 protective atmosphere tubular furnace, slowly heated to 400°C at a heating rate of 2°C / min, and calcined for 4 hours to obtain a Cu / C catalyst.

[0074] Comparative Example 2

[0075] (1) 1.75 g Cu(NO3)2·3H2O and 0.5 g CTAB were dissolved in 30 ml deionized water, respectively, and recorded as solution A; 0.85 g terephthalic acid (H3BDC) was dissolved in 30 ml anhydrous ethanol, and recorded as solution B; the mixtures were stirred evenly, and solution B was added to solution A to obtain a mixed solution, and the mixed solution was placed in a 100 ml hydrothermal reactor with a polytetrafluoroethylene liner and placed in an oven, crystallized at 110°C for 10 h, and then taken out, washed with water and ethanol for 3 times, respectively, and dried in a vacuum oven at 90°C to obtain a Cu-MOF material;

[0076] (2) The Cu-MOF material obtained in step (1) was evenly ground and placed in a N2 protective atmosphere tubular furnace, slowly heated to 1100°C at a heating rate of 2°C / min, and calcined for 2h to obtain a Cu / C catalyst.

[0077] Example of hydrogen production from methanol liquid phase reforming

[0078] Example 10

[0079] The catalyst prepared in Example 1 was used to catalyze the liquid phase reforming of methanol to produce hydrogen, and the reaction process was as follows:

[0080] Step 1: First, 50 mg of the catalyst sample of Example 1 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a mass ratio of 16:27 was added to the reaction system to seal the activated catalyst sample;

[0081] Step 2: Add a small amount of potassium hydroxide to the reaction system to absorb the CO2 produced by the reaction to promote the forward progress of the reaction. Purge the reactor three times with 2MPa inert gas as a protective gas and then seal the reactor to maintain a pressure of 2MPa;

[0082] Step 3: Then the temperature of the reactor was raised to 220°C and maintained for 90 minutes. After the reaction, the reactor was taken out and quickly cooled to room temperature, and the gas phase products were collected. The gas phase products were quantitatively analyzed using gas chromatography with a single-point calibration method.

[0083] Embodiment 11

[0084] The catalyst prepared in Example 2 was used to catalyze the liquid phase reforming of methanol to produce hydrogen, and the reaction process was as follows:

[0085] Step 1: First, 50 mg of the catalyst sample of Example 2 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a mass ratio of 16:27 was added to the reaction system to seal the activated catalyst sample;

[0086] Step 2: Add a small amount of potassium hydroxide to the reaction system to absorb the CO2 produced by the reaction to promote the forward progress of the reaction. Purge the reactor three times with 2MPa inert gas as a protective gas and then seal the reactor to maintain a pressure of 2MPa;

[0087] Step 3: Then the temperature of the reactor was raised to 220°C and maintained for 90 minutes. After the reaction, the reactor was taken out and quickly cooled to room temperature, and the gas phase products were collected. The gas phase products were quantitatively analyzed using gas chromatography with a single-point calibration method.

[0088] Example 12

[0089] The catalyst prepared in Example 3 was used to catalyze the liquid phase reforming of methanol to produce hydrogen, and the reaction process was as follows:

[0090] Step 1: First, 50 mg of the catalyst sample of Example 3 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a mass ratio of 16:27 was added to the reaction system to seal the activated catalyst sample;

[0091] Step 2: Add a small amount of potassium hydroxide to the reaction system to absorb the CO2 produced by the reaction to promote the forward progress of the reaction. Purge the reactor three times with 2MPa inert gas as a protective gas and then seal the reactor to maintain a pressure of 2MPa;

[0092] Step 3: Then the temperature of the reactor was raised to 220°C and maintained for 90 minutes. After the reaction, the reactor was taken out and quickly cooled to room temperature, and the gas phase products were collected. The gas phase products were quantitatively analyzed using gas chromatography with a single-point calibration method.

[0093] Embodiment 13

[0094] The catalyst prepared in Example 4 was used to catalyze the liquid phase reforming of methanol to produce hydrogen, and the reaction process was as follows:

[0095] Step 1: First, 50 mg of the catalyst sample of Example 4 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a mass ratio of 16:27 was added to the reaction system to seal the activated catalyst sample;

[0096] Step 2: Add a small amount of potassium hydroxide to the reaction system to absorb the CO2 produced by the reaction to promote the forward progress of the reaction. Purge the reactor three times with 2MPa inert gas as a protective gas and then seal the reactor to maintain a pressure of 2MPa;

[0097] Step 3: Then the temperature of the reactor was raised to 220°C and maintained for 90 minutes. After the reaction, the reactor was taken out and quickly cooled to room temperature, and the gas phase products were collected. The gas phase products were quantitatively analyzed using gas chromatography with a single-point calibration method.

[0098] Embodiment 14

[0099] The catalyst prepared in Example 5 was used to catalyze the liquid phase reforming of methanol to produce hydrogen, and the reaction process was as follows:

[0100] Step 1: First, 50 mg of the catalyst sample of Example 5 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a mass ratio of 16:27 was added to the reaction system to seal the activated catalyst sample;

[0101] Step 2: Add a small amount of potassium hydroxide to the reaction system to absorb the CO2 produced by the reaction to promote the forward progress of the reaction. Purge the reactor three times with 2MPa inert gas as a protective gas and then seal the reactor to maintain a pressure of 2MPa;

[0102] Step 3: Then the temperature of the reactor was raised to 220°C and maintained for 90 minutes. After the reaction, the reactor was taken out and quickly cooled to room temperature, and the gas phase products were collected. The gas phase products were quantitatively analyzed using gas chromatography with a single-point calibration method.

[0103] Embodiment 15

[0104] The catalyst prepared in Example 6 was used to catalyze the liquid phase reforming of methanol to produce hydrogen, and the reaction process was as follows:

[0105] Step 1: First, 50 mg of the catalyst sample of Example 6 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a mass ratio of 16:27 was added to the reaction system to seal the activated catalyst sample;

[0106] Step 2: Add a small amount of potassium hydroxide to the reaction system to absorb the CO2 produced by the reaction to promote the forward progress of the reaction. Purge the reactor three times with 2MPa inert gas as a protective gas and then seal the reactor to maintain a pressure of 2MPa;

[0107] Step 3: Then the temperature of the reactor was raised to 220°C and maintained for 90 minutes. After the reaction, the reactor was taken out and quickly cooled to room temperature, and the gas phase products were collected. The gas phase products were quantitatively analyzed using gas chromatography with a single-point calibration method.

[0108] Example 16

[0109] The catalyst prepared in Example 7 was used to catalyze the liquid phase reforming of methanol to produce hydrogen, and the reaction process was as follows:

[0110] Step 1: First, 50 mg of the catalyst sample of Example 7 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a mass ratio of 16:27 was added to the reaction system to seal the activated catalyst sample;

[0111] Step 2: Add a small amount of potassium hydroxide to the reaction system to absorb the CO2 produced by the reaction to promote the forward progress of the reaction. Purge the reactor three times with 2MPa inert gas as a protective gas and then seal the reactor to maintain a pressure of 2MPa;

[0112] Step 3: Then the temperature of the reactor was raised to 220°C and maintained for 90 minutes. After the reaction, the reactor was taken out and quickly cooled to room temperature, and the gas phase products were collected. The gas phase products were quantitatively analyzed using gas chromatography with a single-point calibration method.

[0113] Embodiment 17

[0114] The catalyst prepared in Example 8 was used to catalyze the hydrogen production reaction by liquid phase reforming of methanol, and the reaction process was as follows:

[0115] Step 1: First, 50 mg of the catalyst sample of Example 8 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a mass ratio of 16:27 was added to the reaction system to seal the activated catalyst sample;

[0116] Step 2: Add a small amount of potassium hydroxide to the reaction system to absorb the CO2 produced by the reaction to promote the forward progress of the reaction. Purge the reactor three times with 2MPa inert gas as a protective gas and then seal the reactor to maintain a pressure of 2MPa;

[0117] Step 3: Then the temperature of the reactor was raised to 220°C and maintained for 90 minutes. After the reaction, the reactor was taken out and quickly cooled to room temperature, and the gas phase products were collected. The gas phase products were quantitatively analyzed using gas chromatography with a single-point calibration method.

[0118] Embodiment 18

[0119] The catalyst prepared in Example 9 was used to catalyze the liquid phase reforming of methanol to produce hydrogen, and the reaction process was as follows:

[0120] Step 1: First, 50 mg of the catalyst sample of Example 9 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a mass ratio of 16:27 was added to the reaction system to seal the activated catalyst sample;

[0121] Step 2: Add a small amount of potassium hydroxide to the reaction system to absorb the CO2 produced by the reaction to promote the forward progress of the reaction. Purge the reactor three times with 2MPa inert gas as a protective gas and then seal the reactor to maintain a pressure of 2MPa;

[0122] Step 3: Then the temperature of the reactor was raised to 220°C and maintained for 90 minutes. After the reaction, the reactor was taken out and quickly cooled to room temperature, and the gas phase products were collected. The gas phase products were quantitatively analyzed using gas chromatography with a single-point calibration method.

[0123] Embodiment 19

[0124] The catalyst prepared in Example 1 was used to catalyze the hydrogen production reaction by liquid phase reforming of methanol, and the reaction process was as follows:

[0125] Step 1: First, 50 mg of the catalyst sample of Comparative Example 1 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a mass ratio of 16:27 was added to the reaction system to seal the activated catalyst sample;

[0126] Step 2: Add a small amount of potassium hydroxide to the reaction system to absorb the CO2 produced by the reaction to promote the forward progress of the reaction. Purge the reactor three times with 2MPa inert gas as a protective gas and then seal the reactor to maintain a pressure of 2MPa;

[0127] Step 3: Then the temperature of the reactor was raised to 220°C and maintained for 90 minutes. After the reaction, the reactor was taken out and quickly cooled to room temperature, and the gas phase products were collected. The gas phase products were quantitatively analyzed using gas chromatography with a single-point calibration method.

[0128] Embodiment 20

[0129] The catalyst prepared in Example 2 was used to catalyze the hydrogen production reaction by liquid phase reforming of methanol, and the reaction process was as follows:

[0130] Step 1: First, 50 mg of the catalyst sample of Comparative Example 2 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a mass ratio of 16:27 was added to the reaction system to seal the activated catalyst sample;

[0131] Step 2: Add a small amount of potassium hydroxide to the reaction system to absorb the CO2 produced by the reaction to promote the forward progress of the reaction. Purge the reactor three times with 2MPa inert gas as a protective gas and then seal the reactor to maintain a pressure of 2MPa;

[0132] Step 3: Then the temperature of the reactor was raised to 220°C and maintained for 90 minutes. After the reaction, the reactor was taken out and quickly cooled to room temperature, and the gas phase products were collected. The gas phase products were quantitatively analyzed using gas chromatography with a single-point calibration method.

[0133] Embodiment 21

[0134] The catalyst prepared in Example 1 was used to catalyze the liquid phase reforming of methanol to produce hydrogen, and the reaction process was as follows:

[0135] Step 1: First, 50 mg of the catalyst sample of Example 1 was reduced and activated at 250° C. for 2 hours in high-purity hydrogen at a flow rate of 50 mL / min. After the catalyst was cooled to room temperature, 10 mL of a methanol:water mixed solution with a mass ratio of 16:27 was added to the reaction system to seal the activated catalyst sample;

[0136] Step 2: Add a small amount of potassium hydroxide to the reaction system to absorb the CO2 produced by the reaction to promote the forward progress of the reaction. Purge the reactor three times with 2MPa inert gas as a protective gas and then seal the reactor to maintain a pressure of 2MPa;

[0137] Step 3: Then the reactor temperature was raised to 220°C for 90 min. After the reaction, the reactor was taken out and quickly cooled to room temperature to collect the gaseous products. The reactor was then sealed to maintain a pressure of 2 MPa and the reaction was continued at 220°C for 90 min. This process was repeated 10 times. The gaseous products were collected 10 times and quantitatively analyzed using gas chromatography with a single-point calibration method.

[0138] The reaction results of Examples 10-21 are shown in Figure 5 and Figure 6 , wherein SL-1 to SL-9 represent the catalysts used in Examples 10-18, respectively, and DB-1 and DB-2 represent the catalysts used in Examples 19-20, respectively.

[0139] like Figure 5 and Figure 6 As shown, the MOF-derived copper-based catalyst Cu / C prepared in the present invention has a high efficiency in methanol liquid phase reforming hydrogen production capacity under medium and low temperature conditions, and the catalyst is reused several times without a significant decrease in the hydrogen production rate, which also shows that the catalyst prepared in the present invention has good stability.

[0140] like Figure 7 As shown, SL-1 to SL-9 represent the catalysts used in Examples 10 to 18, respectively, and DB-1 and DB-2 represent the catalysts used in Examples 19 to 20, respectively. Figure 7 It is shown that the micro-mesoporous structure Cu / C catalyst of the present invention has a high methanol conversion rate of about 10-15% under low temperature conditions and has good selectivity for H2 and CO.

[0141] The above description is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this field, without departing from the creative concept of the present invention, several improvements and changes can be made, which all fall within the protection scope of the present invention.

Claims

1. A MOF-derived copper-based catalyst, characterized in that: The MOF-derived copper-based catalyst is a micro-mesoporous structure Cu / C, wherein the mesopores are distributed in 3-20nm and the micropores are distributed in 0.1-10.8nm; the MOF-derived copper-based catalyst particle size is 2-15μm; the specific surface area is 25-981m 2 / g; the metal copper particles have a size of 5-500nm and are evenly distributed on the carbon material.

2. The MOF-derived copper-based catalyst according to claim 1, characterized in that The mesopores are distributed in the range of 4.5-16.3 nm, and the micropores are distributed in the range of 0.3-0.5 nm; the MOF-derived copper-based catalyst particle size is 5-10 μm; the specific surface area is 100-800 m 2 / g; the metal copper particle size is 50-300nm.

3. The MOF-derived copper-based catalyst according to claim 2, characterized in that The mesopores are distributed at 10 nm, and the micropores are distributed at 0.4 nm; the MOF-derived copper-based catalyst particle size is 7.5 μm; the specific surface area is 103.2 m 2 / g; the metal copper particle size is 70nm.

4. The method for preparing a MOF-derived copper-based catalyst according to any one of claims 1 to 3, characterized in that: The preparation method of the MOF-derived copper-based catalyst comprises the following steps: (1) Synthesis of copper-based metal organic framework materials (Cu-MOF materials): copper salt, organic ligand, and chelating agent are dissolved in a certain amount of solvent to prepare a mixed solution, the mixed solution is transferred into a reaction container and placed in an oven for crystallization reaction, and after the reaction is completed, the mixed solution is cooled, filtered, washed, and dried to obtain the Cu-MOF material; (2) Preparation of MOF-derived copper-based catalyst: The Cu-MOF material obtained in step (1) is ground evenly and placed in a porcelain boat, which is then placed in a high-temperature tubular furnace containing a protective atmosphere for high-temperature calcination and carbonization treatment. After a period of time, the solid subjected to high-temperature calcination and carbonization treatment is taken out and ground evenly to obtain the MOF-derived copper-based catalyst.

5. The method for preparing a MOF-derived copper-based catalyst according to claim 4, characterized in that: The solvent in step (1) is one or more of deionized water, anhydrous ethanol, methanol, N,N-dimethylformamide, and tetrahydrofuran.

6. The method for preparing a MOF-derived copper-based catalyst according to claim 4, characterized in that: The copper salt in step (1) is one or more of copper nitrate, copper acetate, copper chloride, copper sulfate, and copper acetylacetonate; The organic ligand in step (1) is one or more of trimesic acid, terephthalic acid, isophthalic acid, phthalic acid, aminoterephthalic acid, and nitroterephthalic acid; The chelating agent in step (1) is one or more of polyvinyl pyrrolidone (PVP, Mw=8000-220000), polyethers, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, lauric acid, acetic acid, formic acid, triethylamine, diethylamine, and sodium formate; The protective atmosphere is nitrogen or argon.

7. The method for preparing a MOF-derived copper-based catalyst according to claim 4, characterized in that: The crystallization reaction in step (1) is carried out in a crystallization kettle, in a glass container placed in a water bath or an oil bath, or with ultrasound assistance; the crystallization reaction temperature is 80-180°C.

8. The method for preparing a MOF-derived copper-based catalyst according to claim 4, characterized in that: In step (1), the molar ratio of the copper salt to the organic ligand is 1:(0.4-25), the molar ratio of the copper salt to the solvent is 1:(10-680), and the molar ratio of the copper salt to the chelating agent is 1:(0.5-60).

9. The method for preparing a MOF-derived copper-based catalyst according to claim 4, characterized in that: The high temperature carbonization treatment temperature in step (2) is 300-1000°C, the carbonization time is 1-12h, and the heating rate is 0.5-10°C / min.

10. Use of the MOF-derived copper-based catalyst according to any one of claims 1 to 3 or the MOF-derived copper-based catalyst obtained by the preparation method according to any one of claims 4 to 9, characterized in that: The application is application in the hydrogen production reaction of methanol liquid phase reforming.

Citation Information

Patent Citations

  • Copper-based MOF carbonization derived catalytic material and preparation method and application thereof

    CN109894154A

  • Nitrogen-doped carbon-coated copper catalyst as well as preparation method and application thereof

    CN115770603A

  • Copper-based supported catalyst as well as preparation method and application thereof

    CN116037113A

  • Spherical micro-mesoporous composite material catalyst for hydrogen production by methanol steam reforming as well as preparation method and application of spherical micro-mesoporous composite material catalyst

    CN116196936A

Cited By

  • Copper-carbon composite catalyst, preparation method and application of copper-carbon composite catalyst in methanol liquid phase reforming hydrogen production

    CN122479754A